Association between sarcopenia and hospitalization in community-dwelling older adults, using the SARC-F and SARC-CalF methods: a systematic review protocol. (3rd September 2021) - Ferreira, Aline de Bastos; Filho, Romulo Roosevelt da Silva; Rodrigues, Luciana Pereira; de Souza, Guilherme Vinicius; Noll, Matias; Silveira, Erika Aparecida
Abstract: Background : Sarcopenia is a syndrome highly prevalent in older adults, leading to negative health outcomes such as reduced functionality, increased dependence, hospitalization and mortality. It is diagnosed using high-tech methods that are unavailable to the general population. Thus, it is useful to use low-cost and easily applicable sarcopenia screening methods such as SARC-F or SARC-CalF. However, it is unknown whether sarcopenia, as identified by these methods, is associated with a higher risk of hospitalization in the older adults population. Thus, this systematic review protocol aims to determine whether there is an association between sarcopenia, as diagnosed by the SARC-F and SARC-CalF methods, and hospitalization in community-dwelling older adults. Methods : This study follows the criteria proposed by Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols. We will include studies with an observational design, conducted with community-dwelling older adults (≥ 60 years), that used SARC-F/SARC-CalF as screening tool for sarcopenia, and that presented hospitalization indicators. The following databases will be used: PubMed, Scopus, EMBASE, and Lilacs. Studies will be selected based on title, abstract, and full text. The quality of the included studies will be assessed using "Grading of Recommendations, Assessment, Development, and Evaluation" tool. The risk of bias will be assessed using Downs and Black tool. Results : The results of this research may deepen our knowledge of these two methods and their use for identifying and monitoring sarcopenia. Conclusions : Our research will especially benefit if these tools can discriminate the potential risk of hospitalization in older adults and so contribute to reducing early mortality.